2020
DOI: 10.1016/j.mehy.2020.110089
|View full text |Cite
|
Sign up to set email alerts
|

EMMPRIN/BASIGIN as a biological modulator of oral cancer and COVID-19 interaction: Novel propositions

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 20 publications
(27 reference statements)
0
15
0
3
Order By: Relevance
“…ACE2 presents in the lower respiratory tract of humans and accelerates both the cross‐species and human‐to‐human transmissions. Also, CD147 (Basigin/Emmprin) relates to the immunoglobulin superfamily and is expressed in several tissues and cells, including neuronal and epithelial cells 11–14 . Besides the structural proteins, several nonstructural proteins, like RNA‐dependent RNA polymerase (RdRp), are responsible for duplicating genetic information and making the virus with high mutation ability 15 .…”
Section: Virology and Viral Phasementioning
confidence: 99%
See 1 more Smart Citation
“…ACE2 presents in the lower respiratory tract of humans and accelerates both the cross‐species and human‐to‐human transmissions. Also, CD147 (Basigin/Emmprin) relates to the immunoglobulin superfamily and is expressed in several tissues and cells, including neuronal and epithelial cells 11–14 . Besides the structural proteins, several nonstructural proteins, like RNA‐dependent RNA polymerase (RdRp), are responsible for duplicating genetic information and making the virus with high mutation ability 15 .…”
Section: Virology and Viral Phasementioning
confidence: 99%
“…immunoglobulin superfamily and is expressed in several tissues and cells, including neuronal and epithelial cells. [11][12][13][14] Besides the structural proteins, several nonstructural proteins, like RNA-dependent RNA polymerase (RdRp), are responsible for duplicating genetic information and making the virus with high mutation ability. 15 These properties cause a high diversity of coronaviruses, which can infect different hosts.…”
mentioning
confidence: 99%
“…NRP1 is expressed in the differentiated epithelial cell layers of human normal tongue and in epithelial cells of human healthy salivary glands. The neuropilin-1 receptor is up-regulated in dysplastic epithelium and oral squamous cell carcinoma [ 200 , 201 , 202 , 203 , 204 ]. EMMPRIN expression is also up regulated in oral squamous cell carcinoma.…”
Section: Sars-cov-2 Transmission and Oral Cavitymentioning
confidence: 99%
“…EMMPRIN expression is also up regulated in oral squamous cell carcinoma. Since ACE2 expression is depleted in oral squamous cell carcinoma, EMMPRIN receptor might be taken over for SARS-CoV-2 entry into cancer host cells [ 201 , 205 ]. The oral expression of all these factors indicate that oral cavity may be vulnerable to SARS-CoV-2 invasion.…”
Section: Sars-cov-2 Transmission and Oral Cavitymentioning
confidence: 99%
“…The results showed that upregulation of CD147 receptor in oral squamous cell carcinoma patients made them highly susceptible to COVID-19infection. The binding of the spike protein of coronavirus to CD147 receptor leads to its exhaustion and subsequent reduction in carcinogenesis [ 77 ]. Chitosan oligosaccharide has been shown to downregulate the expression of CD147 receptors in gastric cancer patients and thereby, reducing metastatic potential [ 78 ].…”
Section: Chitosan and Its Derivatives Giving A Tough Fight Against Comentioning
confidence: 99%